Marketing Communication Strategy of Sibolga Community on Pandan Beach Tourism Object Development - Nurul Fatimah; Nursapiah Harahap (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of this research is to determine the Sibolga community's strategy for developing pandanus beach tourism objects. Advertising, direct marketing, public relations, personal selling, and sales promotion are all used in the marketing communication strategy. This study will concentrate on the marketing communication mix used in introducing pandanus beach tourist destinations. Pandan Beach is a popular natural tourist destination in Central Tapanuli Regency. This study employs a qualitative descriptive research method in order to display and explain the phenomena observed in the field. This study's data collection technique is an observation technique, which involves making direct observations on the object of research. Interview and documentation techniques are also used in data collection. Interviews were conducted with a variety of informants, including tour guides, people selling souvenirs, and Pandan Beach managers. According to the findings of this study, Pandan Beach employs a marketing communication mix to increase brand awareness, which includes advertising, personal selling, direct marketing, public relations and publicity, and sales promotion. Pandan Beach advertises on social media to reach domestic tourists, and advertisements are also published in local print media. Meanwhile, direct marketing is carried out by collaborating with Medan travel tours. Personal selling is implemented by all pandan beach managers, and all pandan beach managers and guides are trained in personal selling. All managers also serve as Public Relations officers, whose responsibility it is to maintain relationships between internal and external communities. Meanwhile, Pandan Beach is promoting its products by offering attractive price packages to tourists.